2005
DOI: 10.1590/s0102-33062005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade de herbáceas em microhabitats rochoso, plano e ciliar em uma área de caatinga, Caruaru, PE, Brasil

Abstract: RESUMO -(Diversidade de herbáceas em microhabitats rochoso, plano e ciliar em uma área de caatinga, Caruaru, PE, Brasil). Objetivou-se avaliar a influência da heterogeneidade micro-espacial no aumento da fitodiversidade herbácea em uma área de caatinga de Caruaru, Pernambuco, Brasil. Microhabitats rochosos, planos e ciliares foram selecionados, e nesses foi realizado um levantamento qualiquantitativo das herbáceas ocorrentes em 35 parcelas de 1 m 2 , em cada microhabitat. Todas as ervas nas parcelas foram cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
32
2
24

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 5 publications
(10 reference statements)
11
32
2
24
Order By: Relevance
“…Similar numbers were found by Alcoforado-Filho et al (2003) and Araújo et al (2005) in other areas of the Caatinga. Epiphytes showed a low number, with only three species of Bromeliaceae.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Similar numbers were found by Alcoforado-Filho et al (2003) and Araújo et al (2005) in other areas of the Caatinga. Epiphytes showed a low number, with only three species of Bromeliaceae.…”
supporting
confidence: 91%
“…Fabaceae presented the highest richness of herbaceous species per family (14: 11 in Faboideae and 3 in Caesalpiniodeae), followed by Asteraceae (10), Poaceae (9) and Malvaceae (8). These families were predominant in different habitats of Caatinga, such as rocky, flat and gallery microhabitats (Araújo et al 2005;Reis et al 2006), crystalline and sedimentary areas ), and caatinga s. str. (Costa et al 2009).…”
mentioning
confidence: 99%
“…The herbaceous flora of the "caatinga" vegetation, however, is less well know, although previous studies have demonstrated that it: 1) retains the greater part of the biodiversity of the "caatinga" biome , Araújo 2003; 2) is composed predominantly of terophytes plants, and is therefore most apparent during the rainy season (Pereira et al 1989, Araújo 2003, Reis 2004, Silva 2004; 3) influences the dynamics of the woody vegetation component (Araújo 1998); 4) contains habitat-specific species (Reis 2004, Araújo et al 2005b; 5) flowers and fruits most intensely during the raining season, like the woody vegetation (Pereira et al 1989, Reis 2004, Silva 2004, Feitoza 2004) and 6) has great value as pasture, or for apiculture (Carvalho & Marchini 1999, Sampaio et al 2002, Lorenzon et al 2003. It has been suggested that the herbaceous vegetation has an important role in maintaining the biodiversity of the woody component of the flora, as their roots help maintain the soil seedbank (Araújo 2003, Feitoza 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Araújo et al (2005) afirmam que a umidade, principalmente no solo, tende a favorecer o desenvolvimento da vegetação com porte lenhoso, e característica arbórea e arbustivas.…”
Section: Figura 5 -Drenagem Da Sub-bacia Do Rio Taperoáunclassified